Transaction Costs and Prospects for Public-private Partnership in the Russian Mineral Resourse Sector - Glazyrina, Irina; Lavlinskii, Sergey (International Journal of Economics and Financial Issues, 2017)
An analysis is presented for the current development level of the institution of public-private partnership (PPP) in the mineral resources complex ofRussia. The main focus is on the two PPP models that are most widely used inRussia. The first model is production sharing agreement (PSA). An analysis is conducted of the PSA concept. TheSakhalin2 project is used as an example to show how an inadequate preparation of PSA terms and high transaction costs (TC) can lead to a breach of contract. The second model is applied in production infrastructure development projects financed by the Investment Fund of Russia. This is a Russia-specific model; thus, authors use a special toolkit for its assessment in the paper. Analysis shows that important factor of the project efficiency is an institutional environment. Weakness of institutions and lack of low cost instruments of conflict resolution might be the cause of high transaction costs and environmental damage. The technique applied in the efficiency analysis of concrete partnership arrangements is presented using the examples of the PPP models practiced in Krasnoyarsk Krai and Transbaikal region in Siberia. It can be applied in designing a raw-material base development program involving PPP arrangements. The problem solution generates a cost-sharing arrangement between the state and the private investor, making it possible to optimize the majority of Russian PPP models. Keywords: Mineral resources, public-private partnership, production sharing agreement, transaction costs. JEL Classifications: Q32, O13, C63